OPTIMASI DAN UJI MUTU FISIK FORMULASI MASKER GEL PEEL – OFF KULIT PISANG (Musa paradisiaca L) - Lia Agustina; Dewi Mega Ayu Pertiwi; Ninis Yuliati (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2022)
Kepok banana (Musa paradisiaca L.) is one of the most commonly consumed bananas in Indonesia. Apart from the fruit, the other potentially used is banana peel. Kepok banana peel is rich in flavonoids which has function as antioxidants that protect skin from free radicals. In this study, we optimized and conducted physical characterization for banana peels peel-off gel mask. The aim for this research was to optimize the peel-off gel mask and analized the physical characteristics of peel-off mask gel. The formulation was optimized with different concentration of active substance. The physical characterization was organoleptic observation, homogeneity, pH, dispersibility, adhesion, drying time, irritation and stability assay. Organoleptics observation showed that peel-off gel showed distinctive scent, brownish color and gel-like structure. All preparation were homogenous, pH value dispersibility, adhesion, and drying time was within the required criteria. The peel-off was not irritant as showed from irritation assay. The preparation was also stable during 12 weeks storage under room temperature condition. We conclude that banana peels peel-off gel mask was successfully formulated. Further observation for its effectivity will be required.